HARMONI: A first light spectrograph for the E-ELT - Clarke, F; Thatte, N; Tecza, M; Arribas, S; Bacon, R; Davies, R; Mediavilla, E (Office National d'Etudes et de Recherches Aerospatiales, ONERA, 2011)
We describe the current status of the HARMONI instrument design, which will form the basis for the first-light integral field spectrograph on the European Extremely Large Telescope. We review the phase A design, and highlight current on-going work to evolve the design in-line changing telescope requirements and lessons learned during the Phase A work. We also outline the key science drivers for the instrument, and describe briefly the requirements for the laser tomographic adaptive optics system which is expected to feed HARMONI.